Develop Sinawang Plugin with PjBL in Moodle to Improve Network Administration Competence - Romadhon, Muslich Wahyu; Prismana, I Gusti Lanang Putra Eka; Fauzan Nusyura (Journal of Education Technology and Information System, 2025)
This research aims to design and implement the Sinawang plugin in Moodle as a learning media that supports the application of Project Based Learning (PjBL) in designing the student learning process. In addition, this research also aims to evaluate the impact of the use of learning media in improving the competence of Network System Administration in class XI TKJ students at SMKN 1 Kediri. The Sinawang plugin design process utilizes PHP, Javascript, HTML, and CSS programming languages with the Research and Development (R&D) development model. The test design used in this research is Developmental Testing. The results of media testing through the black box testing method show that all components function properly (valid). Data from the validation of media, lesson plans, materials, and questions show the level of validity successively 88% (very valid), 83% (very valid), 80% (valid), and 83% (very valid). The analysis results showed that the average score of the cognitive test on the posttest (86.6) was higher than the pretest (52.8). Similarly, the mean value of the psychomotor test on the posttest (85.9) was also higher than the pretest (74.5). Based on the paired sample t-test results, the Significance (2-tailed) value obtained for both tests is 0.000, which is smaller than 0.05. Therefore, in accordance with the basis for decision making in the paired sample t-test, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This indicates that there is an increase in student competence in Network System Administration subjects through the use of the "Sinawang" plugin with the application of Moodle-based Project-Based Learning (PjBL).